Sunday

April 20, 2014

April 20, 2014

Posted by **Melanie** on Tuesday, February 22, 2011 at 7:18pm.

1) 3x + y = 6

2x + 3y = 13

2) 2x + 5y - 6 = 0

-2x + y - 2 = 0

3) x + 3y = 6

4x - 5y = 7

- Math -
**MathMate**, Tuesday, February 22, 2011 at 9:55pmI'll solve the first one, leaving you a chance to practice with the rest.

3x + y = 6 .....(1)

2x + 3y = 13 ....(2)

Multiply (1) by 3 and subtract (2) to eliminate y:

9x + 3y = 18 .....(1a)

2x + 3y = 13 .....(2a)

Subtract:

7x = 5

x=5/7 .....(3)

Substitute (3) in 1

3(5/7) + y = 6

y = 6-15/7

=27/7 ....(4)

Substitute (3) and (4) in (2) to check:

2(5/7) + 3(27/7)

=(10+81)/7

=13 OK.

**Related Questions**

Derive - Find the derivative of sin(2x + 3y)= 3xy + 5y-2. I have this so far 1) ...

Math - Please show the solutions! 1.) x+y-2(2x-3y) 2.) x+y/2 - 3x-y/4 + x-5y/8 3...

Rational Expression - (x+1/2x-1 - x-1/2x+1) * (2x-1/x - 2x-1/x^2) (x+1/2x-1 - x-...

math - Solve the systems of equations by elimination. 1. -2x+y=7 2. 2x+y=-9 6x+...

Math Homework - Hello! I need help with these math questions, thanks! :) 1.) ...

math - A linear system may have a unique solution, no solution, or infinitely ...

algebra - solve each system by substitution 1. 6x-3y=-33 2xty=-1 2. 2x-y=7 3x-2y...

algebra 2 - solve each system by substitution 1. 6x-3y=-33 2xty=-1 2. 2x-y=7 3x-...

Math - Ok so you're supposed to solve the system by method of substitution. And ...

Math - Solve the system using any algebraic method. 2x - 2y + z = 3 5y - z = -31...